MODELLING STRAIN-SOFTENING BEHAVIOUR OF CLAYEY SOILS - J.-C. Chai; J. P. Carter; S. Hayashi (International Association of Lowland Technology, 2007)
A method for modelling the strain-softening behaviour of clayey soils under undrained and/or partially drained conditions is proposed and applied to simulate the mechanical behaviour of undisturbed Ariake clay and limestabilized Ariake clay samples under undrained conditions. The proposed method is based on the Modified Cam clay (MCC) model. It is assumed that during the softening process, the strain increments can still be calculated by the MCC model, but the effective stress path is enforced to follow the projection of the critical state line (CSL) in a p’– q plot (i.e., q = M p’ where p’ is mean effective stress, q is deviator stress and M is the slope of the CSL in the p’– q plot). Therefore the method is not completely rigorous in the applied mechanics sense, rather it is a pragmatic approach. The proposed method has been incorporated into a finite element code and its performance was verified by simulating undrained triaxial compression tests. Subsequently, the method has been applied to simulate the mechanical behaviour of both natural and lime-stabilized Ariake clays. Comparing the simulated results with the test data indicates that the method simulated both the shear strain versus deviator stress curve and the effective stress path reasonably well. However, the results also showed that in the case of the lime-stabilized Ariake clay, the adoption of a high initial stiffness under lower confining stress should be considered. It is suggested that the proposed method can be used to analyze geotechnical problems involving strain-softening behaviour with reasonable accuracy.